Differences of drivers' driving performance in simulated driving. - Sze, Seen Kee; Mohd Tamrin, Shamsul Bahri; Goh, Yong Meng (Medwell Publishing, 2009)
The statistics for a 10 years periods (1997-2007) shows an increasing number of road traffic accidents in Malaysia. Amongst, commuting accidents, which involved bus carsh are highest increased from year 2006-2007. Human errors have been identified as main reasons behind these fatal crashes compare to others. This study aims to determine the factors, which cause the differences of driving performance between two driving groups in related with environmental condition and road conditions in a simulated daytime and night-time driving. Fifty healthy male subjects, aged between 23-53 years old were divided into two groups and took part in one of the two different driving sessions (simulated daytime or night time driving). The total length of each simulated driving journey is 250 km. Outcomes were measured in terms of driver’s driving performance (RORI and LSV index) in different of environmental and road conditions. The ambient temperature, Carbon dioxide (CO2) level and lighting conditions were regulated throughout the experiment. The study showed that occupational drivers perform better rather than non-occupational drivers whenever the driving conditions and environmental factors considered. However, no difference of driving performance found between two driving groups in different of road types. Driver’s age and driving experience was significantly correlated with both RORI and LSV index in an overall study. Occupational drivers perform better when considered the driving condition and environmental effect, indicating that drivers with extended age and prior experience tend to perform better.